In the name of national security : Hitchcock, homophobia, and the political construction of gender in postwar America - Corber, Robert J., 1958- (New Americanists., 1993)
In the Name of National Security exposes the ways in which the films of Alfred Hitchcock, in conjunction with liberal intellectuals and political figures of the 1950s, fostered homophobia so as to politicize issues of gender in the United States. As Corber shows, throughout the 1950s a cast of mind known as the Cold War consensus prevailed in the United States. Promoted by Cold War liberals--that is, liberals who wanted to perserve the legacies of the New Deal but also wished to separate liberalism from a Communist-dominated cultural politics--this consensus was grounded in the.